2018
DOI: 10.1371/journal.pone.0203633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intergenerational educational mobility on health of Indian women

Abstract: This study aims to analyse the relationship between intergenerational educational mobility and the overall health of the Indian women. It uses a nationally representative survey, India Human Development Survey (IHDS) 2011–12, and logistic regressions to study this relationship. The sample comprises of women aged 45 years and older. We find that the women experiencing upward intergenerational educational mobility (vis-a-vis their mothers) have significantly higher chances of experiencing good overall health com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Within these vulnerable sections, women are often identified and acknowledged as particularly affected (Bellundagi et al ., 2022). The pervasive gender-based discrimination in India, spanning from the ancient to the current times, results in numerous challenges for women, including in areas of education, occupation and nutrition (Choudhary and Singh, 2018). Also, research on the interlinkages between child outcomes and parental characteristics indicates that children's outcomes, especially in education and health, heavily rely on their mother's educational and health status (Bellundagi et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Within these vulnerable sections, women are often identified and acknowledged as particularly affected (Bellundagi et al ., 2022). The pervasive gender-based discrimination in India, spanning from the ancient to the current times, results in numerous challenges for women, including in areas of education, occupation and nutrition (Choudhary and Singh, 2018). Also, research on the interlinkages between child outcomes and parental characteristics indicates that children's outcomes, especially in education and health, heavily rely on their mother's educational and health status (Bellundagi et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed that these components have anti-oxidant, anti-inammatory, anti-tumor, anti-microbial, anti-obesity, antihyperlipidemic and anti-depressant effects. [1][2][3] Our research results showed that the alkaloids from P. longum (PLA), which mainly contained PPR, PPL, DPPL, piperanine (PPRA) and pellitorine (PLTR), exerted neuroprotective effects in Parkinson's disease (PD) models induced by neurotoxins such as 6hydroxydopamin (6-OHDA), 1-methyl-4-phenyl-1,2,3,6tetrahydropyridine (MPTP), rotenone and lipopolysaccharide (LPS). Furthermore, PPR and PPL could improve cell viability and alleviate motor decits and loss of midbrain dopaminergic neurons in PD cell and mouse models induced by rotenone.…”
Section: Introductionmentioning
confidence: 99%